The Evolution of Autistic-Like and Schizotypal Traits: A Sexual Selection Hypothesis - Del Giudice, Marco; Angeleri, Romina; Brizio, Adelina; Elena, Marco R. (Frontiers in Psychology, 2010)
In this paper we present a new hypothesis on the evolution of autistic-like and schizotypal personality traits. We argue that autistic-like and schizotypal traits contribute in opposite ways to individual differences in reproductive and mating strategies, and have been maintained – at least in part – by sexual selection through mate choice. Whereas positive schizotypy can be seen as a psychological phenotype oriented to high mating effort and good genes displays in both sexes, autistic-like traits in their non-pathological form contribute to a male-typical strategy geared toward high parental investment, low mating effort, and long-term resource allocation. At the evolutionary-genetic level, this sexual selection hypothesis is consistent with Crespi and Badcock’s “imprinted brain” theory of autism and psychosis; the effect of offspring mating behavior on resource flow within the family connects sexual selection with genomic imprinting in the context of human biparental care. We conclude by presenting the results of an empirical study testing one of the predictions derived from our hypothesis. In a sample of 200 college students, autistic-like traits predicted lower interest in short-term mating, higher partner-specific investment, and stronger commitment to long-term romantic relations, whereas positive schizotypy showed the opposite pattern of effects.